(untitled) (Eurasian Medical Research Periodical, 2023)
Nature gives us many, many materials that enhance human health and happiness. Fruits and vegetables are considered as a great hidden bank for many food and therapeutic materials as it contains essential mineral, macro and trace elements and other biological micronutrients necessary for, normal metabolism, immunity, and antioxidants of great importance in internal metabolic reactions and may correct adverse conditions, as results of deficiency or various diseases. This study was designed to investigate the role and effect of a mixture of pomegranate flowers ( punica granatum )and garlic (Allium astiva) flowers as a juice for men. Fifty healthy men, aged between 28-34 years, were given two doses 100 ml each, in the morning and evening, for four weeks. After the end of the period, the liver profile, antioxidants, kidneys profile, and thyroid gland hormones were measured, in addition to the hematological pictures, and blood pressure. These parameters were including, Alanine transference (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), hematological parameters, creatinine concentration, lipid peroxidation (LPO) by measuring g thiobarbituric reactive substance, malondialdehyde (TBAR) thyroid hormones T3and T4, high density lipoproteins (HDL), low density lipoproteins, (LDL)and body mass. The results were impressive in improving the functional performance of each of the liver, kidneys, thyroid gland, blood characteristics and blood pressure, in addition to the antioxidant activities, as the statistical differences between before and after ingestion are highly significant differences (P< 0.001)